IN SILICO STRUCTURAL, EVOLUTIONARY, AND EXPRESSION ANALYSIS OF SMALL HEAT SHOCK PROTEIN (SHSP) ENCODING GENES IN COCOA (THEOBROMA CACAO L.) - P. B. Cao (Journal of Animal and Plant Sciences, 2022)
The small heat shock proteins (sHSP) are the molecular chaperones that play important roles in the development and stress responses of plants. However, the sHSP family has not been well investigated in cocoa (Theobroma cacao L.). In this work, a total of 32 full-length genes encoding putative sHSP proteins were predicted in the cocoa genome. Predicted proteins were ranging from 130 to 269 amino acids. Most of them were intronless or single intron. The cocoa sHSPs were divided into 12 subclasses including seven cytoplasmic (CI–CVII) and five organelles localized subclasses. The 32 cocoa sHSP (TcsHSP) genes were randomly distributed in the entire cocoa genome but chromosome 9 appeared as the hot spot regions for TcsHSPs. Tandem duplication events made a contribution to the expansion of sHSP genes in cocoa. The Ka/Ks values from three CII sHSP genes were ranging from 0.12 to 0.24. Differently, most of the Ka/Ks ratios from 11 CI sHSP genes were greater than 1.0, suggesting the driving change in this group. TcsHSPs were found expressed in all developmental stages with different profiles. This work contributes to providing valuable information on the evolutionary relationship of the sHSP gene family in cocoa which is useful for future investigation of functional characteristics of TcsHSP genes.
Keywords: cocoa (Theobroma cacao L.); gene family; in silico; small heat shock proteins (sHSP)